Relacionamento entre a forma urbana e as viagens a pé - Amancio, Marcelo Augusto (Universidade Federal de São Carlos, 2005)
The objective of this dissertation is to verify if there is a relationship between the characteristics of the urban form and option for walking trips. For this relationship to be studied, the first step was a bibliographic review about the urban form characteristics that might influence the option for walking. Among the methodologies that could be used to evaluate the modal option, a logit-type Discrete Choice Model, was chosen. The data used for the calibration of the model were collected in São Carlos, SP, a Brazilian medium-sized city with around 200 thousand inhabitants. The analyses were developed at census tract level, with a Geographic Information System (TransCAD). Two logit-type models were calibrated. The first one (basic) includes only a socio-economic variable (automobile availability) and the trip length. The second model (expanded) includes, besides the variables of the basic model, information about the characteristic of the urban form in the trip origin sectors. The comparison of the results obtained with the two models, allowed the evaluation of the marginal influence of urban form variables on the mode choice. In general, the expanded model was statistically better then the basic one. The results suggest that urban form characteristics do influence the individuals´ option for walking.
Keywords: Transporte urbano; Logit; Sistemas de informação geográfica; Transporte - transito de passageiros; Forma Urbana; Modelos de escolha discreta; Pedestres; Urban form; Geographic information systems; Discrete choice models; Pedestrians; ENGENHARIAS::ENGENHARIA DE TRANSPORTES